Application of Technology Adoption Model through Utilitarian Information in Ruang Impian Marketing Program - Putri Andari, Dhea Almyra; Marsasi, Endy Gunanto (Jurnal Manajemen, 2023)
Researchers examined a company engaged in interior design providing various facilities from artistry to furniture supplies. This study aims to propose a marketing program to evaluate the marketing carried out by companies through social media. This study used Observation, in-depth interviews, secondary company data, documentation, and descriptive qualitative research methodologies collection. This research resulted in an analysis of the proposal of the Ruang Impian program, a program to do marketing through social media. This program proposal is assisted by the theory of the Technology Acceptance Model with the concept of Utilitarian Information to help companies develop social media. It is hoped that the Technology Acceptance Model with the idea of Utilitarian Confirmation can help the company's marketing develop and become a force for DENTUUM.